A Truce in Criminal Law's Distributive Principle Wars? - Robinson, Paul H. (2020)
Crime-control utilitarians and retributivist philosophers have long been at war over the appropriate distributive principle for criminal liability and punishment, with little apparent possibility of reconciliation between the two. In the utilitarians’ view, the imposition of punishment can be justified only by the practical benefit that it provides: avoiding future crime. In the retributivists’ view, doing justice for past wrongs is a value in itself that requires no further justification. The competing approaches simply use different currencies: fighting future crime versus doing justice for past wrongs.It is argued here that the two are in fact reconcilable, in a fashion. We cannot declare a winner in the distributive principle wars but something more like a truce. Specifically, good utilitarians ought to support a distributive principle based upon desert because the empirical evidence suggests that doing justice for past wrongdoing is likely the most effective and efficient means of controlling future crime.But “doing justice” here is not justice in the deontological desert sense of what moral philosophers think is deserved but rather justice in the “empirical desert” sense that reflects the community’s shared judgments of justice. On the other hand, the two conceptions of desert have an enormous overlap, and it seems likely that empirical desert may be the best practical approximation of deontological desert. Indeed, some philosophers would argue that the two are necessarily the same.By tracking the community’s principles of justice, the system can build “moral credibility” with the community, which allows it to harness the powerful forces of social influence, community support, and internalization of the law’s norms. Empirical research confirms that a criminal justice system perceived by the community as conflicting with their principles of justice is one that provokes resistance and subversion, while a criminal justice system that earns a reputation for reliably doing justice – by tracking shared community principles of justice – is one whose moral credibility inspires greater deference, assistance, and acquiescence, and is more likely to have citizens internalize its norms of what constitutes truly condemnable conduct